PERLINDUNGAN HUKUM TERHADAP KESEJAHTERAAN ANAK Harmonisasi Undang – undang - - Kuswardani; - Chusniatun (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The law is a tool development to all of children welfare. Protection and legal guarantees against children welfare as a consequences Indonesia rule of law, because it is human rights of children.  Law is acts have to in accordance with the Pancasila and UUD NRI 1945, so the acts areharmonious.  This aim of study to descript harmonization of legislation on law protection of children welfare, so that the research is normative legal. The result research show thatharmonization of legislation on law protection of children welfare are not harmonious yet. Lex of children welfare that should be as reference to protect,  to guarantee , but it give the meaning of children welfare is not exstensive,  limited to basic needs, those fisiology needs.. Keywords : law protection, children welfare.